London Clubland - Milne-Smith, A. author. aut Link
XI, 296 p. 9 illus.
Keywords: This work is the first to study the gentlemen's clubs that were an important feature of the Late Victorian landscape, and the first to discover the secret history of clubmen and their world, placing them at centre stage, detailing how clubland dramatically shaped 19th and early 20th-century ideas about gender, power, class, and the city.